Reactive blue dye removal by membrane distillation using PVDF membrane - Chong, K.C.; Lai, S.O.; Thiam, H.S.; Lee, S.S.; Lau, W.J.; Nadzirah, Mohd Mokhtar (Informatics Publishing Limited, 2016)
Background/Objectives: Membrane distillation (MD) is a thermally driven water separation process which has lately attracted the attention from the academics and industries due to its lower energy requirement relative to pressure driven process. The aim of this paper is to study the performance of self-fabricate hollow fiber membrane in reactive blue dye removal by membrane distillation technique. Methods/Statistical Analysis: In this work, the potential use of polyvinylidene fluoride (PVDF) for reactive blue dye removal was study by direct contact membrane distillation (DCMD). The membranes were produced by phase inversion spinning method with 1-methyl-2-pyrrolidone (NMP) solvent and ethylene glycol (EG) additive. The membranes were characterized in term of membrane morphology, porosity, liquid entry pressure and hydrophobicity. Findings: Relative to the pristine membrane, PVDF membrane with additive was discovered to be possessed enhanced membrane characteristics, i.e. higher liquid entry pressure and larger pore size. In terms of membrane stability, the experimental results demonstrated that the PVDF membranes with EG as additive were able to generate consistent flux, while maintaining a superior rejection rate of reactive blue dye. Application/Improvements: The result in this work shown that PVDF membrane with EG as additive possesses a superior permeate flux performance and rejection rate which suggested that this membrane possesses the prospect to be applied in the industrial textile wastewater treatment.